The influence of person-job fit and person-organisation fit on employees job performance (Journal of Business Management and Accounting, 2012)
The objective of this study is to examine the relationship between person-job fit, personorganisation fit and job performance. The study was conducted on employees of MNC status organisations. Questionnaire was administered to 300 respondents, who were technical employees of the organisations. However, only 180 responses were received and used for analysis. Data were analysed using correlation and regression analysis. Findings indicate that person-job fit and person-organisation fit have a significant and positive influence on job performance. Lastly, this paper also provides suggestions for organisations on ways to increase job performance.